Promoting Indonesian Culinary Art Pocong Pancong Malang through Social Media Content - Hellyani, Catharina Aprilia; Adriana, Erica; Putrianto, Novenda Kartika (Journal of Community Practice and Social Welfare, 2024)
Social media content has become a global phenomenon, offering a unique platform for users worldwide to share information, entertainment, and engage with others. Creative and engaging content has the potential to capture attention and even go viral. In Indonesia, one such trend gaining significant attention is 'Pocong Pancong.' This community engagement initiative aims to promote Indonesian culinary arts, specifically Pocong Pancong from Malang, through social media content. The success of this engagement is determined by the engagement rate, which serves as an indicator of effectiveness. The engagement process consists of three phases: preparation, execution, and evaluation. In the preparation phase, the engagement team plans and discusses the profile of Pocong Pancong, formulates the project's vision and mission, and collaborates with the Pocong Pancong MSME (Micro, Small, and Medium Enterprise) partner. The execution phase forms the core of the project. During this phase, the team creates diverse social media content about Pocong Pancong, including product introductions, flavor variations, information on booth locations, the history of pancong cake, and interactive Q&A sessions. These efforts aim to provide valuable insights, educate the public, and engage consumers. The effectiveness of the engagement is measured by the increase in the Instagram account engagement rate, which rises from 1.046 to 1.148 by June 23, 2023. This positive change reflects the favorable community response to the content shared by the engagement team.